Device and method for dynamic image display of financial transaction operation data. (19th November 2021) - Yan, Jingdong; Liu, Wuwei
This article aims to improve the visibility of data in the financial process transactions, provide data support for transaction decisions and ensure the safety of the operation process. This research mainly discusses the device and method for displaying financial transaction operation data in dynamic images. The equipment is divided into an early warning module, a user interaction module, an intelligent management module and a monitoring module. The research results showed that during the test period, the average transmission efficiency of archive logs was 77%, and the average transmission efficiency of activity logs was 79%. This shows that the dynamic image display system device for financial transaction operation data has excellent performance and can provide users with real-time transaction information.